20:30 BRUXSELS TALKS: A SCRIPT FOR A FUTURE FICTION RADIO SHOW - Anthoni, Ellen; Balwani, Khushboo; Schoffelen, Jessica; Hannes, Karin (Art/Research International)

(untitled) (University of Alberta, 2021)
On the 23rd of January 2020, a radio talk show of the future, 20:30 Bruxsels Talks, took place in Brussels. With fictional guests and artists from the year 2030, it discussed how the transition to a climate-proof city had happened since 2019. The body of this article is the script of this fiction piece, produced by BrusselAVenir and BNA-BBOT. In the introduction we explain the relationship between the field of futures studies and fiction, we frame 20:30 Bruxsels Talks within futures studies, and highlight the potential of fiction for knowledge creation and dissemination. By publishing the script, we hope to inspire researchers, changemakers and artists to explore fiction as a method, as a format and as a space, to trigger conversation and imagination, and engage citizens to take up a role in shaping the cities they live in.